TECHNOLOGY AND MATHEMATICS: AUGMENTED REALITY AS A FACILITATOR OF SPATIAL UNDERSTANDING (REMUNOM, 2025)
This article addresses the difficulties students face in understanding abstract mathematical concepts, particularly in Spatial Geometry and functions, when exposed to traditional teaching methodologies. It proposes the use of interactive digital technologies, with an emphasis on Augmented Reality (AR), as a resource to facilitate learning through the visualization and manipulation of three-dimensional objects. An analysis of studies on educational applications (such as GeoTransform3D, AppiRAmide, GeometriAR, and GeoGebra) demonstrates that these technologies contribute to increased student motivation, comprehension, and engagement. The study also presents a teaching sequence using GeoGebra, aiming to make instruction more visual, interactive, and meaningful, aligning with the needs of new generations and highlighting the importance of continuous teacher training for the effective integration of these tools.